Access to Endovascular Treatment in Remote Areas: Analysis of the Reperfusion Treatment Registry of Catalonia. Issue 5 (May 2016) - Pérez de la Ossa, Natalia; Abilleira, Sònia; Dorado, Laura; Urra, Xabier; Ribó, Marc; Cardona, Pere; Giralt, Eva; Martí-Fàbregas, Joan; Purroy, Francisco; Serena, Joaquín; Cánovas, David; Garcés, Moisés; et al.
Abstract : Background and Purpose—: Since demonstration of the benefit of endovascular treatment (EVT) in acute ischemic stroke patients with proximal arterial occlusion, stroke care systems need to be reorganized to deliver EVT in a timely and equitable way. We analyzed differences in the access to EVT by geographical areas in Catalonia, a territory with a highly decentralized stroke model. Methods—: We studied 965 patients treated with EVT from a prospective multicenter population-based registry of stroke patients treated with reperfusion therapies in Catalonia, Spain (SONIIA). Three different areas were defined: (A) health areas primarily covered by Comprehensive Stroke Centers, (B) areas primarily covered by local stroke centers located less than hour away from a Comprehensive Stroke Center, and (C) areas primarily covered by local stroke centers located more than hour away from a Comprehensive Stroke Center. We compared the number of EVT×100 000 inhabitants/year and time from stroke onset to groin puncture between groups. Results—: Baseline characteristics were similar between groups. Throughout the study period, there were significant differences in the population rates of EVT across geographical areas. EVT rates by 100 000 in 2015 were 10.5 in A area, 3.7 in B, and 2.7 in C. Time from symptom onset to groin puncture was 82 minutes longer in group B (312 minutes [245–435]) and 120 minutes longer in group C (350 minutes [284–408]) compared with group A (230 minutes [160–407]; P <0.001). Conclusions—: Accessibility to EVT from remote areas is hampered by lower rate and longer time to treatment compared with areas covered directly by Comprehensive Stroke Centers.